Communication Skill-Based Writing Instruction (Csbwi) to Promote Students Writing Ability - Ayu Andriyaningsih; Vike Aprilianin Marwintaria Saputri; Burmansah; Komang Sutawan; Sutanto (Syntax Corporation, 2023)
This study examined the effect of communication skill-based writing instruction on the student writing ability. The researcher used a pretest-posttest experimental group design. The research was conducted from April to May 2023 in the Jinarakkhita Buddhist College Bandar Lampung. The researchers used the Statistical Package for Social Science (SPSS) version 25 program to analyze the data. A rubric score was used to analyze and measure the students' narrative text writing ability before and after treatment. The student's writing ability improved from 49.9 to 65.1. In addition, the researcher found that students who previously struggled to write now have a growing understanding of how to gather information and confidently use CSBWI in their writing. Therefore, it is critical to use a suitable and effective method to assist students in overcoming the difficulty of their writing achievement.